Model Pengembangan Anggur Bogor Berbasis Local Knowledge dengan Pendekatan Agribisnis di Ciptagelar - Nada Fadilah; Ikhwana Dwiyanti; Nur Fauziah; Yusalina Yusalina (Jurnal Ilmu Pertanian Indonesia, 2022)
Anggur bogor (Smilax macrocarpa) is one of the endemic plants that grows in Kasepuhan Ciptagelar, Halimun Salak mountain. This plant has the potential to be developed as a cultivated plant. However, until now, the local community has not made any cultivation efforts. Therefore, the development of anggur bogor is important to maintain its sustainability by utilizing the local knowledge possessed by the Kasepuhan Ciptagelar indigenous people. This study aims to examine the potential of Bogor wine development related to local knowledge of the Kasepuhan Ciptagelar indigenous people and to formulate a Bogor wine development model with an agribusiness system approach. Data collection was done by literature study. Then, the study was carried out using a systematic review method by analyzing 23 journal articles, theses, dissertations, and news with relevant keywords. The results obtained indicate that the community adheres to local customs in agriculture and the development of Bogor wine based on local knowledge of the community based on the agribusiness approach can be focused on Leuweung Bukaan or sampalan. Keywords: endemic, local knowledge, systematic review